2023
DOI: 10.1007/s10552-023-01762-3
|View full text |Cite
|
Sign up to set email alerts
|

The impact of the COVID-19 pandemic in the clinical assistance to breast cancer patients

Inês Ribeiro,
Bárbara Peleteiro,
José Luís Fougo

Abstract: Purpose We aimed to disclose the impact of the pandemic on breast cancer patients in a specialized breast cancer center (BCC). Methods A total of 501 breast cancer patients with a first appointment in the BCC from April 1st, 2019 to March 31st, 2021 were divided into four consecutive periods of 6 months. Data from the homologous semesters was compared. Patients with an appointment in the BCC during the study period were eligible for the secondary aim of ou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“…Fritsch et al [ 36 ] reported that COVID-19 decreased the number of screenings for mammography. Ribeiro et al [ 37 ] disclosed that COVID-19 had a significant impact on breast cancer patients. Teresa Ardillo et al [ 38 ] mentioned a confusion due to influenza vaccines versus COVID-19 mRNA vaccines might have caused more fear among cancer patients than the public.…”
Section: Introductionmentioning
confidence: 99%
“…Fritsch et al [ 36 ] reported that COVID-19 decreased the number of screenings for mammography. Ribeiro et al [ 37 ] disclosed that COVID-19 had a significant impact on breast cancer patients. Teresa Ardillo et al [ 38 ] mentioned a confusion due to influenza vaccines versus COVID-19 mRNA vaccines might have caused more fear among cancer patients than the public.…”
Section: Introductionmentioning
confidence: 99%